Behavioral responses to earthquake shaking: Video footage analysis of the 2016 Kaikōura earthquake in Wellington, Aotearoa New Zealand. Issue 3 (August 2022) - Vinnell, Lauren J; Inch, Piata; Johnston, David M; Horspool, Nick
Initiatives such as the ShakeOut earthquake drill (run nationally in Aotearoa New Zealand since 2012) are effective at teaching the protective actions "drop, cover, and hold" which can reduce the likelihood of injury during earthquakes. However, our understanding of human behavior during actual shaking is limited. Previous work has used retrospective self-reports to explore what actions people take during and immediately after an earthquake. While informative, such data is exposed to biases common in these types of methods. It is therefore important to complement the previous research with more objective data. This research builds on previously-developed methods of analyzing Closed Circuit Television (CCTV) footage to examine actions taken during the 2016 Kaikōura earthquake at Wellington International Airport, Aotearoa New Zealand. Only one of the 68 codable individuals was observed to undertake "drop, cover, and hold" as recommended in New Zealand, although a quarter took some kind of protective action (e.g. dropping or covering). The majority responded by standing, walking, looking around, or helping those near them. Because this earthquake had distinct P-wave and S-waves, we were able to examine changes in behavior caused by increases in shaking intensity. Among the 36 individuals who could be observed during the strong S-wave jolt, 27 changed their behavior; 11 changed from not protecting themselves to taking at least one protective action, and another 8 who were already undertaking at least one protective action took a further one or more steps to protect themselves. Among the 10 people observed to have an uncontrolled response to the sudden increase in shaking intensity, nine were taking no actions to protect themselves demonstrating the importance of taking protective actions before the arrival of strong shaking. This article presents key considerations for CCTV analysis and useful observations of behavior during earthquake shaking which can help to reduce injuries and fatalities.